2021
DOI: 10.1186/s12951-021-00873-w
|View full text |Cite
|
Sign up to set email alerts
|

Expression and mechanism of exosome-mediated A FOXM1 related long noncoding RNA in gastric cancer

Abstract: Background Forkhead box protein M1 (FOXM1) is an oncogene regulating tumor growth and metastasis. Exosome was suggested to mediate cell communication by delivering active molecules in cancers. However, the existence of FOXM1 in circulating exosomes and the role of exosome FOXM1 in gastric cancer (GC) were not clear. This study aims to investigate the potential role of FOXM1 related long noncoding RNA (FRLnc1) in exosomes in GC. Results The prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Exosomal FRLnc1 from gastric cancer cells can effectively augment cell proliferation, viability, and migration in receiver cancer cells [123] (Figure 4 and Table 2). Although direct targets of FRLnc1 remain to be identified, FRLnc1 is known to upregulate the level of TGFB1 and TWIST, favoring migration in vitro and lung metastasis in vivo in gastric cancer [180].…”
Section: Frlnc1 and Pcgem1mentioning
confidence: 99%
“…Exosomal FRLnc1 from gastric cancer cells can effectively augment cell proliferation, viability, and migration in receiver cancer cells [123] (Figure 4 and Table 2). Although direct targets of FRLnc1 remain to be identified, FRLnc1 is known to upregulate the level of TGFB1 and TWIST, favoring migration in vitro and lung metastasis in vivo in gastric cancer [180].…”
Section: Frlnc1 and Pcgem1mentioning
confidence: 99%
“…Zhang et al found that GC cells treated with the exosomes containing FOXM1-related lncRNA (FRLnc1) can enhance GC cell proliferation and migration. The FRLnc1 knockdown in GC cells can induce cell cycle arrest and cell apoptosis ( Zhang et al, 2021 ). In addition, some studies have shown that the exosomal lncRNAs derived from cancer cells can regulate the cancer immune microenvironment, such as immunosuppressants and immune escape, to promote cancer progression.…”
Section: Biological Roles Of Exosomal Lncrnas In Gastrointestinal Cancermentioning
confidence: 99%
“…Lnc-FRLnc1 is significantly up-regulated in the serum and serum exosomes of patients with gastric cancer. The up-regulation of FRLnc1 expression is closely related to lymph node metastasis and TNM staging ( 71 ). The high expression of Lnc-SCHLAP1 is significantly related to the adverse clinicopathological characteristics of prostate cancer, including grade group, high pT staging, aggressive cribriform growth/prostatic intraductal carcinoma, and reactive stroma ( 72 ).…”
Section: Overview Of Lncrnasmentioning
confidence: 99%